A salt-reduction smartphone app supports lower-salt food purchases for people with cardiovascular disease: Findings from the SaltSwitch randomised controlled trial. (29th August 2020) - Eyles, Helen; McLean, Rebecca; Neal, Bruce; Jiang, Yannan; Doughty, Robert N; McLean, Rachael; Ni Mhurchu, Cliona
Abstract: Background: SaltSwitch is an innovative smartphone application (app) that enables shoppers to scan the barcode of a packaged food and receive an immediate, interpretive, traffic light nutrition label on the screen, along with suggestions for lower salt alternatives. Our aim was to determine the effectiveness of SaltSwitch to support people with cardiovascular disease to make lower salt food choices. Design: Six-week, two-arm, parallel, randomised controlled trial in Auckland, New Zealand (2 weeks baseline and 4 weeks intervention). Methods: Sixty-six adults with diagnosed cardiovascular disease (mean (SD) age 64 (7) years) were randomly assigned in a 1:1 ratio to either the SaltSwitch smartphone app or control (usual care). The primary outcome was the salt content of household packaged food purchases during the 4-week intervention (g/MJ). Secondary outcomes were the saturated fat content (g/MJ), energy content (kJ/kg) and expenditure (NZ) of household food purchases; systolic blood pressure (mmHg), urinary sodium (mg) and use and acceptability of the SaltSwitch app. Results: Thirty-three participants with cardiovascular disease were allocated to the SaltSwitch intervention, and 33 to the control group. A significant reduction in mean household purchases of salt was observed (mean difference (95% confidence interval), −0.30 (−0.58 to −0.03) g/MJ), equating to a reduction of ∼0.7 g of salt per person per day during the 4-week intervention phase. There were no significant between-group differences in any secondary outcomes (all P > 0.05). Conclusions: The SaltSwitch smartphone app is effective in supporting people with cardiovascular disease to make lower salt food purchases. A larger trial with longer follow-up is warranted to determine the effects on blood pressure. Trial registration: Australian New Zealand Clinical Trials Registry https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=365784&isReview=true ACTRN12614000206628